Deglacial climate and relative sea level changes forced the shift from eolian sandsheets to dunefields in southern Brazilian coast - Rodrigues, Fernanda C. G.; Giannini, Paulo C. F.; Fornari, Milene [UNESP]; Sawakuchi, Andre O. (Elsevier B.V., 2020)
Quaternary sea level and climate changes can promote spatio-temporal shifts in themorphology of coastal eolian depositional systems. A shift of depositional features such as from sandsheets to dunefields occurs as response to a disequilibrium condition in the system promoted by changes in accumulation space and sediment supply balance. On the other hand, the eolian system migration, with maintenance of morphological patterns, points to an equilibrium conservation under minor variations in the external controlling factors of the system. The Santa Catarina coast in southern Brazil hosts widespread active and stabilized eolian depositional systems with varied morphology. In this study, geomorphologic and stratigraphic changes of eolian deposits of the southern coast of Santa Catarina were constrained by optically stimulated luminescence (OSL) dating. This allowed to assess how coastal eolian systems responded to late Quaternary climate and sea level changes. Eolian sandsheets initiated around 22 ka ago, during the Last Glacial Maximum (LGM), and persisted during most of the deglacial period under conditions characterized by sea level lowstand, wider exposition of shelf sediments, more continental and drier climate and scarcer vegetation cover in the study setting. The shift from eolian sandsheets to dunefields occurred approximately at 6 ka ago and marks the establishment of coastal conditions in the study setting. The development of dunefields since the middle Holocene would result from eolian system disequilibrium in response to a condition characterized by sea level highstand, wetter climate and denser vegetation cover. The maintenance of a dunefield morphology since 6 ka ago, despite its onshore migration, indicates a new equilibrium between accumulation space and sediment supply. Sandsheets evolved to dunefields around 6 ka ago when the coastline stabilized and the accumulation space was limited by onshore vegetation growth, favoring eolian sediment aggradation. The precipitation ridge in the inner margin of the dunefield has been successively stabilized, abandoned and repositioned seaward, accompanying the coastal progradation since 4 ka ago. The decreasing migration rate of dunefields since 4 ka ago is attributed to rainfall reduction, which deplete fluvial sediment supply to coastal systems and, therefore, slow down the coastal progradation rate. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Eolian coastal systems; Morphological changes; LGM